2011
DOI: 10.1371/journal.pntd.0001422
|View full text |Cite
|
Sign up to set email alerts
|

A LigA Three-Domain Region Protects Hamsters from Lethal Infection by Leptospira interrogans

Abstract: The leptospiral LigA protein consists of 13 bacterial immunoglobulin-like (Big) domains and is the only purified recombinant subunit vaccine that has been demonstrated to protect against lethal challenge by a clinical isolate of Leptospira interrogans in the hamster model of leptospirosis. We determined the minimum number and location of LigA domains required for immunoprotection. Immunization with domains 11 and 12 was found to be required but insufficient for protection. Inclusion of a third domain, either 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
91
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(107 citation statements)
references
References 36 publications
12
91
1
3
Order By: Relevance
“…Despite the low challenge doses used in this study, culture and qPCR results of kidney tissue from all animals, LigA7-13 immunized or not, were positive for leptospires. This result is consistent with previous studies showing that LigA immunization afforded protection from lethality but not renal infection (26,30). It is worth noting that our qPCR method involved TaqMan quantitation of the number of lipL32 gene copies per gram of kidney tissue, a method that has previously been applied to blood and urine (38,43).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Despite the low challenge doses used in this study, culture and qPCR results of kidney tissue from all animals, LigA7-13 immunized or not, were positive for leptospires. This result is consistent with previous studies showing that LigA immunization afforded protection from lethality but not renal infection (26,30). It is worth noting that our qPCR method involved TaqMan quantitation of the number of lipL32 gene copies per gram of kidney tissue, a method that has previously been applied to blood and urine (38,43).…”
Section: Discussionsupporting
confidence: 89%
“…As in an earlier study, we found that an endpoint criterion of weight loss of Ն10% of the animal's maximum body weight was extremely useful, because a decrease in body weight was the earliest observable sign of clinical leptospirosis (30). Further support for the importance of body weight in animal models of leptospirosis comes from our finding that the weight of animals that survived challenge was also useful as an indication of underlying renal health.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations